COMPARATIVE ANALYSIS AND IMPACT OF VARIOUS ENTOMOTOXIC NANOPARTICLES AGAINST Sitophilus oryzae - Ch. Muhammad Shahid Hanif; Hafiz Muhammad Aatif; Muhammad Zeeshan Mansha; Zahid Mahmood Sarwar; Kamran Ikram; Qamar uz Zaman; Ibrahim Al-Ashkar; Muhammad Kamran; El-Sabagh Ayman (Journal of Animal and Plant Sciences, 2026)
Rice, an important cereal crop of Pakistan suffers 10 to 18% loss each year during harvesting, threshing, transportation, and storage. Several insect pests attack the grains during storage, but Sitophilus oryzae is one of the most destructive insect pests of rice grains, which causes substantial losses under warm climatic conditions. Conventional control practices such as use of chemical insecticides and fumigants have led to the resistance development in storage insect pests. Moreover, they also exert hazardous effects on human health and environment. This study evaluated the entomotoxic potential of zinc oxide (ZnO), titanium dioxide (TiO₂), and aluminum oxide (Al₂O₃) nanoparticles (NPs) against adult Sitophilus oryzae under controlled laboratory conditions. Custom-synthesized NPs with distinct surface properties viz., hydrophilic, hydrophobic, and lipophilic were tested at three concentrations (0.5, 1.0, and 2.0 g kg⁻¹ of rice grains), alongside untreated controls. The experiment was laid out in a completely randomized design (CRD) following a factorial arrangement, with each treatment replicated five times. After four days of aluminum oxide (1 g kg⁻¹) application, 90% of mortality of S. oryzae was recorded, while titanium oxide and zinc oxide showed similar results (85-90% mortality) with 2 g kg⁻¹ dose rate after 14 days of application. In short, it is preferred to use titanium oxide and zinc oxide than aluminum oxide which exhibits hazardous impacts on stored grains. Furthermore, titanium oxide and zinc oxide also have antimicrobial properties and can protect the stored grains from both insect pests as well as infection caused by microbes.
Keywords: Nano particles; Sitophilus oryzae; DE; Biosafety; residual toxicity